2012
DOI: 10.1155/2012/767501
|View full text |Cite
|
Sign up to set email alerts
|

Association of Oxidative Stress Markers with Atherogenic Index of Plasma in Adult Sickle Cell Nephropathy

Abstract: This paper evaluates the association of oxidative stress and atherogenic index of plasma in order to assess the cardiovascular risk in Sickle cell nephropathy especially as lipoprotein levels are lower in SCD than non-SCD patients. Antioxidant enzymes, malondialdehyde(MDA), urea, creatinine, and glomerular filtration rate were evaluated in 110 confirmed sickle cell disease patients: 65 males in steady state, aged21.1 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…e increased production of ROS in SCD can modify the response to a variety of pathophysiological conditions including inflammation, hypoxia, metabolism of drugs or alcohol, and deficiency in antioxidant enzymes. Reactive oxygen species can cause significant damage to biomolecules since membrane lipids readily react with ROS resulting in lipid peroxidation [24]. Our results demonstrated negative significant correlation between TG, LDL-C, HDL-C, and FRAP or GsH confirming that the accumulation of lipid will lead to the reduction of antioxidant defenses.…”
Section: Discussionsupporting
confidence: 55%
“…e increased production of ROS in SCD can modify the response to a variety of pathophysiological conditions including inflammation, hypoxia, metabolism of drugs or alcohol, and deficiency in antioxidant enzymes. Reactive oxygen species can cause significant damage to biomolecules since membrane lipids readily react with ROS resulting in lipid peroxidation [24]. Our results demonstrated negative significant correlation between TG, LDL-C, HDL-C, and FRAP or GsH confirming that the accumulation of lipid will lead to the reduction of antioxidant defenses.…”
Section: Discussionsupporting
confidence: 55%
“…This observation is similar to previous reports from Nigeria [8], Egypt [9] and Qatar [5]. The decrease in antioxidant enzyme levels and activity could be explained by their susceptibility to ROS-induced oxidation [13, 14].…”
Section: Discussionsupporting
confidence: 91%
“…This finding may suggest that the overabundance of oxidative stress leads to consumption or inactivation this protective cofactor [13, 14]. Oxidative damage may alter both the structure and the function of the glomerulus due to its effects on mesangial and endothelial cells [8, 15]. Oxidative stress has been reported to oxidize angiotensinogen and convert it to angiotensin II (ATII) and to increase secondary angiotensin type 1 receptor (AT1R)-mediated generation of transforming growth factor-beta (TGFβ) in the kidney in SCA; excessive AT1R signaling causes SCA glomerulopathy [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…(16 ) and Emokpae et al (17) who found a significant association between AI and MA. This may have been caused by the fact that the study subjects came from different populations.…”
Section: Discussionmentioning
confidence: 92%
“…This may have been caused by the fact that the study subjects came from different populations. Our study was conducted on healthy subjects, whereas the study by Amirkhizi et al, (15) Linna M et al (16) and Emokpae et al (17) were carried out on pre-hypertensive women, subjects with hyperlipidemia, and subjects with adult sickle cell nephropathy.…”
Section: Discussionmentioning
confidence: 99%